Modelling asset management of railway overhead line equipment - Kilsby, P.; Remenyte-Prescott, Rasa; Andrews, John D. (2016)
The overhead line equipment (OLE) is a critical sub-system of the 25kV AC overhead railway electrification system. There is a need to evaluate OLE asset management strategies through a whole life cost analysis that considers degradation processes and maintenance activities of the OLE components so that the investment required to deliver the level of performance desired by railway customers and regulators can be based on evidence from modelling results. A Petri Net model is proposed to simulate the degradation, failure, inspection and maintenance of the main OLE components and to calculate various statistics associated with the cost and reliability of the system over its whole life. The Petri Net considers all the main OLE components in one model and can simulate both fixed interval and risk based maintenance regimes. To allow such processes to be modelled accurately and efficiently, High Level Petri Net features are used. The model developed is the first of its kind, in such detail, for OLE and the applicability of Petri Nets for modelling many processes on a large system, containing numerous components, is shown.